A handbook "risk communication during global health emergencies for nurses" - Aung, Khin Thandar; Ahmad, Norfadzilah; Saiful Suhardi, Mohd Iman; Mohd Ali, Noor Azizah; Mohd Fadzil, Suhaiza (Eliva Press, 2024)
This handbook equips nurses with the knowledge and skills for effective risk communication during global health emergencies. It introduces core concepts, emphasises their importance, and guides nurses on how to apply principles of risk communication in emergencies. Manage information effectively, aligning with relevant theories. Communicate risks clearly in community settings. By completing the handbook, nurses will gain the ability to implement risk communication strategies during emergencies. Discuss information management based on risk communication models. Effectively communicate risks within communities. The handbook offers a comprehensive overview and includes: Further readings are needed for in-depth exploration of concepts. Pre-test to assess existing knowledge. Post-test to evaluate learning outcomes (passing score: 70%).